Oswajanie śmierci czy apoteoza życia? Umieranie dzieci w powieściach Bracia Lwie Serce A. Lindgren i Pasiasta żyrafa Ala W. Krapiwina - Radosz, Joanna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present article aims at analysing the topic of children’s death in children’s books of the acknowledged authors: Astrid Lindgren’s The Brothers Lionheart and Vladislav Krapivin’s Alik the Striped Giraffe. The core of the research consists in the approach to the phenomenon of premature death as seen by both authors. The elements of the fictional universe, especially space, time and characters, in terms of constructing the particular approach to death and, by such, influencing the young reader are analysed. Moreover, the paper makes an attempt to interpret the plot as either taming the fear of the death or glorifying the life and objecting to the idea of death of children as a whole.